Tourism policy instruments: an empirical analysis of Portuguese local governments - Costa, Cláudia S. (2014)
Tourism activity is intensely subject to market failures and, naturally, requires government intervention (Dimitris, Aimilia and George, 2005; Fayos-Sola, 1996; Fleischer and Felsenstein, 2000; Hartley and Hooper, 1993; Michael, 2001; Monge-González, River and Tijerino, 2010; Scott, 2011; Sinclair, 1998; Smeral, 1998; Wanhill, 2005). However, government intervention is itself a source of policy failure. With this in mind, the research aims at analyzing the importance of public policy tools as an approach to solving public problems related with market failures, while considering possible negative impacts of the intervention itself. These public policy tools have been applied to several policy areas. This work extends these analyses to the context of tourism and applies the instrument typology presented by Weimer and Vining (2005) to fill an important gap in the literature and provide a broader typology of tourism policy tools. In addition, it is evaluated the impact of tourism policy tools in tourism management at the Portuguese municipal level